Forever is a feeling [compact disc] - Dacus, Lucy, 1995- (Geffen Records, 2025)
Following a career-defining run with boygenius that earned her three Grammy Awards, Lucy Dacus's fourth solo studio album explores falling in and out of love, the tumult of desire, and larger than life romance. Across 13 tracks that range from lush arrangements to simple declarations, Dacus makes a serious inquiry into what it looks like to dedicate one's life to true love, and a valiant attempt to capture the elusive, fleeting feeling of forever.